8th International Conference on Strength Training (Norwegian School of Sport Sciences, 2012)
The major goal of this international scientific conference is to present and discuss the most current research concerning strength and power training. The subject matter of the conference not only includes information related to training athletes and individuals interested in general fitness, but also benefits of resistance training for elderly and diseased populations. The multi-disciplinary approach of the conference makes it applicable to clinical and health professionals as well as coaches and athletes.In addition to the presentation of the most current research and information related to the many aspects of strength and power training, the conference also offers an excellent opportunity to exchange information and ideas with colleagues from all over the world.